Learning styles according to Entwistle model and their relationship to mathematical excellence among scientific fifth-grade female students - Sultan Naithel, Maysoon; Fouad Jawad, Lina (Edelweiss Applied Science and Technology, 2024)
The objective of the present study is to determine the nature and direction of the correlation between mathematical excellence and learning styles as defined by the Entwistle, model in fifth-grade scientific female students. The descriptive correlational approach was implemented by the two researchers to accomplish the research objectives. A scale was developed to assess the learning styles of female students in the sample in accordance with the Entwistle, model. : (Knowledge, understanding, application, analysis, synthesis, evaluation, systematic thinking, creativity), and the research community was determined by the female students of the scientific fifth grade in the morning preparatory and secondary schools of the General Directorate of Education of Baghdad/Al-Karkh I, which were chosen randomly and consisted of (204) students, the data were statistically analyzed using the (23-SPSS) program, and the t-test was employed to calculate the arithmetic mean, the hypothesized average of the scale, the standard deviation, the Cronbach alpha equation, and the Pearson correlation coefficient of the students in order to confirm the validity and reliability of the two tools. The researchers obtained a variety of results, such as the statistically significant correlation between mathematical excellence among fifth-grade scientific female students and each learning style according to the Entwistle, model. This suggests that the female students in the study have well-developed mathematical excellence. The researchers propose that comparable investigations be implemented at different educational levels.